The bromance book club - Adams, Lyssa Kay (Adams, Lyssa Kay. Bromance book club., 2019)
The first rule of book club: You don't talk about book club. Nashville Legends second baseman Gavin Scott's marriage is in major league trouble. He<U+2019>s recently discovered a humiliating secret: his wife Thea has always faked the Big O. When he loses his cool at the revelation, it<U+2019>s the final straw on their already strained relationship. Thea asks for a divorce, and Gavin realizes he<U+2019>s let his pride and fear get the better of him. Welcome to the Bromance Book Club. Distraught and desperate, Gavin finds help from an unlikely source: a secret romance book club made up of Nashville's top alpha men. With the help of their current read, a steamy Regency titled Courting the Countess, the guys coach Gavin on saving his marriage. But it'll take a lot more than flowery words and grand gestures for this hapless Romeo to find his inner hero and win back the trust of his wife.